2020
DOI: 10.1101/2020.03.01.20029884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary epidemiological analysis on children and adolescents with novel coronavirus disease 2019 outside Hubei Province, China: an observational study utilizing crowdsourced data

Abstract: BackgroundThe outbreak of coronavirus disease 2019 continues to expand across the world.Though both the number of cases and mortality rate in children and adolescents is reported to be low in comparison to adults, limited data has been reported on the outbreak with respect to pediatric patients. To elucidate information, we utilized crowdsourced data to perform a preliminary epidemiologic analysis of pediatric patients with COVID-19 MethodsIn this observational study, data was collected from two open-access, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…An analysis of more than 2000 child patients with suspected or confirmed COVID‐19 in Hubei, China, found that over 90% presented as asymptomatic or with mild to moderate symptoms 9 . A summary of paediatric cases reported with COVID‐19 is presented in Table 1 7,9‐45 . These numbers are likely to be under‐representative, as there is not universal testing of the whole population for the presence of COVID‐19.…”
Section: Covid‐19mentioning
confidence: 99%
“…An analysis of more than 2000 child patients with suspected or confirmed COVID‐19 in Hubei, China, found that over 90% presented as asymptomatic or with mild to moderate symptoms 9 . A summary of paediatric cases reported with COVID‐19 is presented in Table 1 7,9‐45 . These numbers are likely to be under‐representative, as there is not universal testing of the whole population for the presence of COVID‐19.…”
Section: Covid‐19mentioning
confidence: 99%
“… 16 , 17 In one study, Henry et al reported that the reduced susceptibility among pediatric patients is still unknown. 18 In addition to underreporting, a combination of epidemiologic and biologic factors may account for the lower rate of infection. Children have a less mature form of the ACE-2 receptor which the SARS-CoV-2 virus’ S protein binds which might decrease their susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The most common presentation is short history of prodrome with myalgias, malaise, cough and low-grade fever. As per the case series from China, only 40-70% of the pediatric patients have fever as an initial presentation [2][3][4]. During the second week of illness, progression of the disease gradually leads to difficulty in breathing.…”
Section: Clinical Coursementioning
confidence: 99%